Association between work stress and mental health in Chinese public health workers during the COVID-19 epidemic: mediating role of social support and self-efficacy - Dong, Yinqiao; Zhu, Qianqian; Chang, Ruijie; Wang, Rongxi; Cai, Yong; Huang, Hong (Frontiers in Public Health, 2023)
Little is known about the mediating mechanisms underlying the association between work stress and mental health, especially among primary public health workers (PHWs). We aimed to evaluated the association between work stress and mental health among PHWs, and explore the mediating roles of social support and self-efficacy.: A large-scale cross-sectional survey was conducted among 3809 PHWs from all 249 community health centers in 16 administrative districts throughout Shanghai, China. Pearson correlation and hierarchical linear regression were used to explore the associations among work stress, social support, self-efficacy and mental health. Structural equation modeling (SEM) was conducted to examine the mediation effects.The prevalence of depression and anxiety symptoms among primary PHWs was 67.3% and 55.5%, respectively. There is a significant positive direct effect of work stress on mental health (β=0.325, P<0.001). Social support and self-efficacy partially mediated the relationship between work stress and mental health, respectively.Meanwhile, the chained mediating effects of social support and self-efficacy also buffered the predictive effects of work stress on anxiety and depression symptoms (β=0.372, P<0.001).Conclusions: Work stress has significant direct and indirect effects on mental health among primary PHWs. Enhancing social support and self-efficacy may be effective psychological interventions to mitigate the effects of work-related stress on mental health. These findings highlight the severity of mental health problems among primary public health workers and provide new evidence for early prevention and effective intervention strategies.